2.45-GHz microwave plasma sources using solid-state microwave generators. Collisional-type plasma source. Issue 1 (2nd January 2017) - Latrasse, Louis; Radoiu, Marilena; Lo, Juslan; Guillot, Philippe
ABSTRACT: The availability of high power solid-state microwave generators opens new directions in plasma generation with applications in industrial plasma processing at low pressure. The optimization of the plasma production line, i.e. from the microwave generator to the plasma source, is a requisite to enable the scaling-up while ensuring a robust control of the equipment. In addition to the electron cyclotron resonance (ECR) coaxial microwave plasma source previously reported, a collisional plasma source was developed for processing at 1–100 Pa. Similar to the ECR plasma source, the results of measurements performed with the collisional plasma source demonstrate that plasma density and uniformity are highly dependent on the microwave power, the reactor pressure and the distance to and between plasma sources. It was demonstrated that the collisional plasma source can attain very high plasma densities, i.e. >10 12 cm −3 in argon and >10 11 cm −3 in molecular gases like O2, N2, air, H2, making it suitable for high deposition rate plasma-enhanced chemical vapour deposition or for high density production of reactive species. A comparison of the two microwave plasma sources is given for the main plasma parameters; the choice of one plasma source over the other depends on the intended process/operating pressure.